High Tuberculosis density incidence rate in Matched Unrelated Allogeneic stem cell transplantation recipients in the state of São Paulo, Brazil - Marcelo Nóbrega Litvoc; silvia F costa; Fabio Eudes Leal; Diogo Boldim Ferreira; Max Igor Banks Ferreira Lopes; Ligia Capuani; Vanderson Geraldo Rocha (Mediterranean Journal of Hematology and Infectious Diseases)
Background: There is limited data regarding Tuberculosis in hematopoietic stem cell transplantation (HSCT), especially in endemic countries.